If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3x + 5 = 5(2x + -3) Reorder the terms: 5 + 2x + 3x = 5(2x + -3) Combine like terms: 2x + 3x = 5x 5 + 5x = 5(2x + -3) Reorder the terms: 5 + 5x = 5(-3 + 2x) 5 + 5x = (-3 * 5 + 2x * 5) 5 + 5x = (-15 + 10x) Solving 5 + 5x = -15 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 5 + 5x + -10x = -15 + 10x + -10x Combine like terms: 5x + -10x = -5x 5 + -5x = -15 + 10x + -10x Combine like terms: 10x + -10x = 0 5 + -5x = -15 + 0 5 + -5x = -15 Add '-5' to each side of the equation. 5 + -5 + -5x = -15 + -5 Combine like terms: 5 + -5 = 0 0 + -5x = -15 + -5 -5x = -15 + -5 Combine like terms: -15 + -5 = -20 -5x = -20 Divide each side by '-5'. x = 4 Simplifying x = 4
| 4z-2(z+6)=7z+8 | | 5x^2-30x-80= | | 6y+2y=9-3y | | 2x-5x=5+4y | | 5x-x+7x= | | 3x+2=5-x | | 2x=3x-2 | | 502.4=12(3.141592654)(r)+(3.141592654)(r^2) | | 4p^2q+q^3-q^2=0 | | 502.4=12(pi)(r)+(pi)(r^2) | | 4-2n=5n+n | | 33=P(0.06)3 | | 6+2n=4n-3n | | 8v+1=7v-2-0 | | 9-(4y-9)=8-5y | | -21c+19=21c-1 | | -36+3x^2=0 | | 3x^2*x=108 | | 18=15-n+3 | | 0.5(6x+12)=1.3-(x+2) | | 6x-y=17 | | 2-2n=n+15 | | -20=10-6+n | | -16=5+n | | 6(3-2z)+13z-4= | | 4+3n=1-4n | | 36+p-4=p | | 3x-9=x+4 | | v(v+1)=272 | | 2-8v=2v+8 | | =6x^2+5xy-25y^2 | | 5m+1=3m+9 |